Think + Think + … Think = Overthinking / Ch’ng Pei Eng ... [et al.] - Ch’ng, Pei Eng; Chew, Yee Ming; Cheng, Siak Peng; Abdullah, Mohd Haris Ridzuan Ooi (Unit Penerbitan JSKM, 2020)
The term “Overthink” is defined as the action of using one’s mind to think too much about something; or putting too much time into thinking about or analyzing something (Merriam-Webster’s online dictionary, 2020). Being an overthinker, a person is trying to control the future or constantly thinking about negative situations (Optimal Positivity, 2020). It is one of the most unhelpful mental habits. Overthinking is actually associated with uncertainty. A person probably feels that his future is being attacked or harmed, either physically or emotionally and he will try very hard to solve problems in the head; or he might be spending so much time ruminating or his mind is going over and over the same thing about something that has happened in the past. In a study conducted by Arbor (2003), she found that 73% of adult in the age group between 25 and 35-year-olds are overthinkers, while 52% of adult in the age group of 45- to 55-year-olds are overthinkers. She also found that female tends to think too much as compared to male.